Strategi Pemasaran Produk Wisata Desa Sesaot Dalam Menarik Minat Wisatawan - Ni Made Wulandari; Hj. Erviva Fariantin; Faizatul Fajariah (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This research is a qualitative research with an ethnographic approach strategy that aims to analyze the marketing strategy of Sesaot Village tourism products in attracting tourists. This study took 10 (ten) informants, namely the West Lombok Tourism Office, the Head of Sesaot Village, 2 (two) Tourism Managers, 3 (three) Business Actors, 3 (three) communities. This study used several data collection techniques, namely in-depth interviews, observation, and documentation. The interview technique was carried out in an unstructured manner using an interview guide. The marketing strategy used by Sesaot Tourism Village is in the form of developing tourist destination objects or products, promoting through social media or the internet, increasing accessibility, and improving services. The result of the development of tourism products in Sesaot Tourism Village is the construction of several new photo spots that previously did not exist in the PUREKMAS area, various facilities such as toilets, and berugak have been provided to maintain the comfort of tourists when visiting. It is known that tourist interests can change along with the development of tourist attractions, when a tourist attraction has new things, tourists will feel interested and think about trying it.